The influence of cooperative learning strategy on social studies pre-service teachers' attitudes towards cybercrime prevention - Omojemite, Matthew Damilola; Cishe, Elphina Nomabandla (Universitas Negeri Yogyakarta, 2024)
This study investigates the influence of cooperative learning strategy on Social Studies pre-service teachers' attitudes toward cybercrime prevention. The study employed a quasi-experimental research design of the pre-test, post-test, and control group design. The population comprised pre-service teachers enrolled in Social Studies education departments across three universities in the Southwest region of Nigeria. A multistage sampling procedure was employed, selecting intact classes from each university. The research utilized a comprehensive set of instruments, including the Cooperative Learning Strategy Guide and Lecture Note (CLSG), Conventional Method Guide and Lecture Note (CMG), and Attitude to Cybercrime Prevention Scale (ACPS). Data analysis was conducted using descriptive and inferential statistics. All Hypotheses were tested at a significance level of 0.05. The findings showed that using cooperative learning strategies positively affects Social Studies pre-service teachers' attitudes toward cybercrime prevention. This approach encourages active engagement, collaboration, group discussions, problem-solving, and sharing learning experiences. These results revealed the necessity for tailored approaches to address attitude change effectively. Integrating cooperative learning strategies into higher education can help pre-service teachers take a proactive approach to cybercrime prevention. This will improve their knowledge and skills while promoting a safer digital learning environment for students.